Smartphone Technology for Household Management - Mulyaningsih Mulyaningsih; Eti Kusmiati; Ieke Sartika Iriany; Rostiena Pasciana (Jurnal Organisasi dan Manajemen, 2023)
Purpose – Technology adoption is commonplace in household management to, among others, save time and effort in completing household chores today. This is marked by the burgeoning use of various household tools for cooking, washing, and the use of cell phones. This study aimed to analyze the behavior of household technology users and its effect on household management productivity.  Methodology – In this study, the method used was qualitative, with a survey-descriptive approach. Data were collected through interviews with 19 purposively selected informants, observation, and documentation study and then analyzed in stages, i.e., reduction, display, analysis, and conclusion drawing. Findings – The results showed that the use of technology in household management boosted housewives’ productivity, which in turn affected the roles of other family members. Furthermore, it was also confirmed that most housewives could use technology to form happy, peaceful, and prosperous families. Based on these findings, the use of technology has a favorable influence on how housewives execute their duties in managing households, particularly with regard to the object under investigation. Originality – This research develops the role of women in household management supported by the use of technology.